PENGARUH DISCIPLINE DAN JOB SATISFACTION TERHADAP EMPLOYEE PERFORMANCE PADA DINAS LINGKUNGAN HIDUP DAN KEHUTANAN YOGYAKARTA DENGAN WORK FROM HOME SEBAGAI VARIABEL MODERATING PADA MUSIM PANDEMI - Haslinda, Nurul; Zuraida, Lukia (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The research aims to analyze the impact of discipline and job satisfaction on the performance of the Yogyakarta Environment and Forestry Service employees with work from home as a moderating variable during the pandemic season. The population in this researchis all of Dinas Lingkungan Hidup dan Kehutanan Yogyakarta s employee which consists by civil servants and auxiliary workers. A simple random sampling technique was applied to the sampling of this research. The number of samples used in this research uses the Slovin formula with an error rate of 1 percent. The number of samples was 121. The research data processing was carried out using Smart PLS4.0 software. Data analysis using SEM model. Research proves that (1) Discipline has a significant impact on the performance of employees of the Yogyakarta Environment and Forestry Service. (2) Job satisfaction has a significant impact on the performance of employees of the Yogyakarta Environment and Forestry Service. (3) WFH has a significant impact on the performance of the Yogyakarta Environment and Forestry Service employees during the pandemic season. (4) Discipline has a unidirectional but not significant impact on the performance of the Yogyakarta Environment and Forestry Service employees with WFH as moderator during the pandemic season. (5) Job satisfaction has no significant impact on the performance of the Yogyakarta Environment and Forestry Service employees with WFH as a moderator during the pandemic season.